Perilaku Membuang Sampah pada Siswa Sekolah Dasar 85 Palembang - Maria Ulfah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Presentation of 24.84 million in Indonesia In 2021, school students produce organic and inorganic waste every day. The results of monitoring and evaluation at SDN 85 Palembang City in 2022, 15% of 25% of the achievement targets in subjects have integrated 3R materials, the habit of sorting waste according to its type has not become behavior with the results of socialization monitoring reaching 10% of the 20% achievement target, and reducing plastic waste from the target achievement of 20% there is no change in the physical condition of the environment in reducing the accumulation of plastic waste. This shows it is important to maintain behavior and health as a manifestation of the need for better health. Objective: Factors related to the behavior of throwing garbage in its place by fifth grade students at SDN 85 Palembang City in 2022. The study was conducted from May 25, 2022 to June 02, 2022. Methods: The research design used a quantitative approach with a cross sectional and a sample of 65 respondents with simple random sampling technique. Results: The results showed that there is a relationship between knowledge and behavior p value (0.044), there is no relationship between gender and behavior p value (0.924), and there is no relationship between attitude and behavior p value (0.065). Suggestion: Suggestions for SDN 85 Palembang to optimize the role of UKS as information and education regarding environmental care and to conduct intensive socialization of waste sorting methods to all school residents. For further researchers to be able to develop more in-depth research on factors related to behavior.